Phenotypic and genomic characterization of the Antarctic bacterium Gillisia sp. CAL575, a producer of antimicrobial compounds. - Maida I; Fondi M; Papaleo MC; Perrin E; Orlandini V; Emiliani G; de Pascale D; Michaud L; Lo Giudice A; Romoli R; Bartolucci G; Fani R.; et al. (Extremophiles, 2014)
Microorganisms from Antarctica have evolved particular strategies to cope with cold. Moreover, they have been recently reported as producers of antimicrobial compounds, which inhibit the growth of other bacteria. In this work we characterized from different viewpoints the Gillisia sp. CAL575 strain, a psychrotrophic bacterium that produces microbial volatile organic compounds involved in the growth inhibition of Burkholderia cepacia complex members. Sequencing and analysis of the whole genome of Gillisia sp. CAL575 revealed that it includes genes that are involved in secondary metabolite production, adaptation to cold conditions, and different metabolic pathways for the production of energy. All these features make Gillisia sp. CAL575 a possible tool for biotechnology.